PENGARUH PROFITABILITAS, SOLVABILITAS, REPUTASI AUDITOR, UKURAN PERUSAHAAN, KANDUNGAN LABA, DAN JENIS INDUSTRI PADA KETIDAKTEPATWAKTUAN PUBLIKASI LAPORAN KEUANGAN DI PT BURSA EFEK INDONESIA PERIODE 2007 - 2009 - WIRAKUSUMA, MADE GEDE; MANIK CINDRAWATI, PUTU (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 2 (2011))
The usefulness of financial report would decrease if it is not timely reported. The purpose of this study is to examine the impact of profitability, solvency, auditor reputation, company size, earnings content, and industry type on late publication of financial report on Indonesia Stock Market during period of 2007-2009. The hypotheses are tested using multiple regression technique. The results show that auditor reputation and company size significantly affect the late publication of financial reports of companies listed on Indonesia Stock Market during 2007-2009. Other variables, i.e profitability, solvency, and earnings information content do not affect the late publication. The control variable, industry type, also does not have any impact on the late financial report publication of the listed companies.
Keywords: auditor reputation, profitability, solvency, earnings.